Possibilities of Magnetic Resonance and Computed Tomography in Early Detection of Joint Changes In Rheumatoid Arthritis Disease - Botirbekov Abdurashid Nazarqulovich (Zien Journals, 2023)
Early detection of joint damage by MRI and CT methods relative to the stage of the disease in patients with rheumatoid arthritis observed
Keywords: Magnetic resonance imaging and computed tomography; joint changes